Formability of a wire arc deposited aluminium alloy - Silva, C. M. A. (2018)
This paper is focused on the formability of the aluminium alloy AA5083 deposited by wire arc additive manufacturing (WAAM). The presentation draws from metal deposition with a robotic welding system to mechanical and formability characterization by means of standard test specimens. Finite element analysis using porous metal plasticity is utilized to model strain hardening and the changes in porosity due to plastic deformation. Results show that the deposited aluminium alloy has excellent ductility and that its final stress response can significantly improve as a result of strain hardening. Voids resulting from metal deposition are closed by negative values of stress-triaxiality resulting from compression forming. The investigation is also a step towards understanding the potential of including intermediate forming operations in conventional wire arc additive manufacturing (WAAM), consisting of metal deposition and machining.